Well at work : creating wellbeing in any workspace - Sternberg, Esther M. (Little, Brown Spark, 2023)
"Whether you work in a traditional office or a corner of your bedroom, staying well at work need not be a luxury. But wellness at work isn't just about staying physically healthy; it's also about reducing stress and improving mood, focus, energy, and productivity. Well at Work reveals how to optimize our workspaces for wellbeing across the seven domains of integrative health: stress and resilience, movement, sleep, relationships, environment, nutrition, and spirituality, and even the air we breathe. Along the way, you'll meet the scientists and doctors, designers and architects, and building science professionals who are striving to make workplaces more conducive to wellbeing. And you'll glimpse into the future of the workplace, where artificial intelligence and the metaverse will help us create environments that respond to our individual needs"--